Urbach Tower: Integrative structural design of a lightweight structure made of self-shaped curved cross-laminated timber. (October 2021) - Bechert, Simon; Aldinger, Lotte; Wood, Dylan; Knippers, Jan; Menges, Achim
Abstract: Recent development in research and practice for curved cross-laminated timber (CLT) opens up novel and interesting possibilities for applications of slender surface-active shell structures in architecture. Such typologies provide advantageous structural behaviour allowing for efficient and lightweight structures while simultaneously determine the envelope and space of a building. The high degree of prefabrication combined with a sustainable and renewable building material makes CLT an ecological and economic solution for future construction. This paper presents the design development and construction of the Urbach Tower for the Remstal Gartenschau 2019: a structure made from high curvature CLT components on a building scale. This research contribution illustrates a sophisticated integrative design to construction process emphasizing computational and structural design, fabrication and detailing for curved timber components in complex spatial structures. The authors further explore the structural potential of self-shaped curved CLT investigating the influence of curvature radius on the load-bearing behaviour of the tower structure. The Urbach Tower translates these technical developments into practice arising at the intersection of digital innovation and scientific research.